2001
DOI: 10.1007/3-540-48224-5_70
|View full text |Cite
|
Sign up to set email alerts
|

The Buffer Minimization Problem for Multiprocessor Scheduling with Conflicts

Abstract: We consider the problem of scheduling a sequence of tasks in a multi-processor system with conflicts. Conflicting processors cannot process tasks at the same time. At certain times new tasks arrive in the system, where each task specifies the amount of work (processing time) added to each processor's workload. Each processor stores this workload in its input buffer. Our objective is to schedule task execution, obeying the conflict constraints, and minimizing the maximum buffer size of all processors. In the of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…Bar-Noy et al [7] suggested a different algorithm that simulates the greedy algorithm in the continuous model and is also Θ(log m)-competitive. Chrobak et al [9] studied the more general problem of minimizing the length of the longest queue in a continuous model where queues can be emptied subject to conflict constraints.…”
Section: Side Resultsmentioning
confidence: 99%
“…Bar-Noy et al [7] suggested a different algorithm that simulates the greedy algorithm in the continuous model and is also Θ(log m)-competitive. Chrobak et al [9] studied the more general problem of minimizing the length of the longest queue in a continuous model where queues can be emptied subject to conflict constraints.…”
Section: Side Resultsmentioning
confidence: 99%
“…In particular, they showed how to use cup emptying to produce "fair" job schedules. Chrobak et al [7] introduced a generalization of cup emptying and applied it to multiprocessor scheduling with conflicts between tasks; there is subsequent work by, e.g., Bar-Noy et al [3], Koga [18], and Rote [23]. In the problem, the player can empty more than one cup at a time, but there is a conflict graph between cups.…”
Section: Background and Related Workmentioning
confidence: 99%
“…From state (1, 1) it is not possible to communicate on b because only T 1 is ready to communicate, not T 2 (T 2 is also connected to b). Also at state (1, 1), T 1 can terminate by taking the transition τ 1 and moving to (3,1).…”
Section: An Examplementioning
confidence: 99%
“…Chrobak et al [1] schedule tasks in a multiprocessor environment to minimize maximum buffer size. Our algorithm does not add scheduling constraints to the problem: it reduces the total buffer size without affecting the schedule, and thereby not affecting the overall speed.…”
Section: Related Workmentioning
confidence: 99%